Service users' experiences and views of support for decision‐making. (23rd February 2020) - Webb, Paul; Davidson, Gavin; Edge, Rosalie; Falls, David; Keenan, Fionnuala; Kelly, Berni; McLaughlin, Aisling; Montgomery, Lorna; Mulvenna, Christine; Norris, Barbara; Owens, Aine; Shea Irvine, Rebecca
Abstract: This article presents the findings from a qualitative, participatory research project which explored how people with intellectual disabilities and/or mental health problems have, or have not been, supported to make their own decisions. The aim of the research is to help inform how supported decision‐making, as required by Article 12 of the UN Convention on the Rights of Persons with Disabilities, can be effectively operationalised. The project provides an overview of experiences of support as well as identifying which supports are valued. It was conducted between July 2017 and July 2018 and was a partnership between disabled people, service providers and a University. It involved peer researchers interviewing 41 people with mental health problems and/or intellectual disabilities, in community settings, about their experiences and views of support. The key findings include that decision‐making is a central aspect of people's lives. Participants discussed the positive role which decision‐making can have but also how it felt when they were not supported to make their own decisions. Participants said that there were three main things that make decision‐making harder: the type of decision; the role of other people; and what the outcome might be. Time was consistently identified as a very important factor. In terms of support, people said that they would like: practical support including more accessible information; emotional support including someone to talk to; and sometimes the options to choose from. There was very little mention of existing, more formal processes of support such as advance decisions or care planning. The peer researcher aspect of the project was valued by participants. The main implications of the research are for how support for decision‐making should be provided including the need for an individualised approach as the support needed varies across decisions, time and people.